Shanghaied into the future: the Asianization of the future Metropolis in post-Blade Runner cinema - Ceresa, Marco (Journal of Architecture and Urbanism, 2017)
The cliched 1930–1950 Western cinematic images of Shanghai as a fascinating den of iniquity, and, in contrast, as a beacon of modernity, were merged in Fritz Lang’s Metropolis. As a result, a new standard emerged in science fiction films for the representation of future urban conglomerates: the Asianized metropolis. The standard set by this film, of a dark dystopian city, populated by creatures of all races and genetic codes, will be adopted in most of the representations of future cities in non-Asian cinema. This article traces the representation of Shanghai in Western cinema from its earliest days (1932– Shanghai Express) through Blade Runner (1982) to the present (2013– Her). Shanghai, already in the early 1930s, sported extremely daring examples of modern architecture and, at the same time, in non-Asian cinema, was represented as a city of sin and depravity. This dualistic representation became the standard image of the future Asianized city, where its debauchery was often complemented by modernity; therefore, it is all the more seedy. Moreover, it is Asianized, the “Yellow Peril” incarnated in a new, much more subtle, much more dangerous way. As such, it is deserving of destruction, like Sodom and Gomorrah.